ANALYSIS OF ORGANIZATIONAL AND ECONOMIC ASPECTS OF THE FUNCTIONING OF TOURISM ENTERPRISES IN KHMELNYTSKYI REGION - ZHURBA, Ihor; TSVIHUN, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the organizational and economic characteristics of tourism enterprises in the Khmelnytskyi region under current conditions marked by economic instability, geopolitical challenges, and transformation of consumer demand. The study provides a comprehensive analysis of the structure, scale, and dynamics of tourism development in the region over recent years. Using statistical data and regional reports, the authors identify key trends in tourism flows, business activities, and investment attractiveness. Special attention is paid to the assessment of both quantitative and qualitative indicators that determine the efficiency of tourism enterprises, including financial performance, employment rates, service quality, and customer satisfaction. The condition of tourism-related infrastructure—such as transport accessibility, accommodation facilities, and information centers—is analyzed in detail, along with an overview of the available human capital and professional training programs for industry personnel. The article highlights the main organizational and managerial problems encountered by tourism businesses, especially those arising from the need to adapt to new economic realities, digitalization, and growing competition. Challenges such as outdated management practices, insufficient marketing strategies, and limited support from local authorities are thoroughly discussed. Based on this analysis, the authors propose practical recommendations to enhance the strategic management of tourism enterprises and improve coordination between stakeholders at the regional level. The study’s findings have significant implications for policymakers, business owners, and academic researchers. It contributes to the development of more effective regional tourism policies and offers a roadmap for strengthening the competitiveness and resilience of the tourism industry in Khmelnytskyi region. The article may also serve as a valuable educational resource for students and educators specializing in tourism, economics, and regional planning.